Strategi Kepala Sekolah dalam Meningkatkan Profesionalisme Guru di SMPN 2 Telukjambe Timur Karawang - Yayu Rukmini; Oyoh Bariah; Achmad Junaedi Sitika (Pendidikan Agama Islam STIT Palapa Nusantara, 2022)
Basically, the principal's goal to improve teacher professionalism at SMPN 2 Teluk Jambe Timur in determining the direction of the development of the progress system in school institutions cannot be separated from the responsibility and cooperation of every human resource in the school in carrying out the process of activities in the field of education, with the principle goal in preparing learning programs. and increasing professional skills for teachers so that they can be included in training, seminars, courses, and workshops without resorting to policy development, policy implementation, and policy evaluation. As a result, several programs to improve teacher skills will be in accordance with the school's vision, mission, and goals. Therefore, a strategy is needed to increase teachers at SMPN 2 Telukjambe Timur Karawang. The method used in this research is a qualitative research by applying naturalistic studies. Researchers used data collection techniques with the following methods: observation, interviews, and documentation. while the approach used in this study is a qualitative naturalistic analysis. So that the findings show an increase in teacher professionalism by the principal to make his work more effective, having professional expertise and skills in carrying out his professional duties as a professional teacher by attending seminars, training courses, and workshops. As well as other facilities that have not been fulfilled so that they can be completed by covering the limitations for an educator in trying to improve soft skills in the field of activities ranging from sports and other fields of art and dance.